Gothic for Girls : Misty and British Comics - Round, Julia (Book collections on Project MUSE., 2019)
Today fans still remember and love the British girls' comic Misty for its bold visuals and narrative complexities. Yet its unique history has drawn little critical attention. Bridging this scholarly gap, Julia Round presents a comprehensive cultural history and detailed discussion of the comic, preserving both the inception and development of this important publication as well as its stories. Misty ran for 101 issues as a stand-alone publication between 1978 and 1980 and then four more years as part of Tammy. It was a hugely successful anthology comic containing one-shot and serialized stories of supernatural horror and fantasy aimed at girls and young women and featuring work by writers and artists who dominated British comics such as Pat Mills, Malcolm Shaw, and John Armstrong, as well as celebrated European artists. To this day, Misty remains notable for its daring and sophisticated stories, strong female characters, innovative page layouts, and big visuals. In the first book on this topic, Round closely analyzes Misty's content, including its creation and production, its cultural and historical context, key influences, and the comic itself. Largely based on Round's own archival research of this comic and richly illustrated with previously unpublished photos, scripts, and letters, this book uses Misty as a lens to explore the use of Gothic themes and symbols in girls' comics and other media. This study also draws on new interviews with many of the retired and forgotten comics creators involved in this comic, including Pat Mills, Wilf Prigmore, and its editorial team Jack Cunningham and Ted Andrews, who have never previously spoken about the comic.